The Proline Regulatory Axis and Cancer - Phang, James M. (Frontiers in Oncology, 2012)
Studies in metabolism and cancer have characterized changes in core pathways involving glucose and glutamine, emphasizing the provision of substrates for building cell mass. But recent findings suggest that pathways previously considered peripheral may play a critical role providing mechanisms for cell regulation. Several of these mechanisms involve the metabolism of nonessential amino acids, for example, the channeling of glycolytic intermediates into the serine pathway for one-carbon transfers. Historically, we proposed that the proline biosynthetic pathway participated in a metabolic interlock with glucose metabolism. The discovery that proline degradation is activated by p53 directed our attention to the initiation of apoptosis by proline oxidase/dehydrogenase. Now, however, we find that the biosynthetic mechanisms and the metabolic interlock may depend on the pathway from glutamine to proline, and it is markedly activated by the oncogene MYC. These findings add a new dimension to the proline regulatory axis in cancer and present attractive potential targets for cancer treatment.